Effects of light intensity and nitrogen source on pac choi (Brassica rapa l.), and interaction with the diamondback moth (Plutella xylostella l.). - Johnson, Wendy Ann (Kansas State University, 2011)
Greenhouse studies were conducted to examine direct effects of light intensity and nitrogen source on primary and secondary metabolism of pac choi (Brassica rapa L. var. chinensis cv. ‘Mei Qing Choi’) and indirect effects on diamondback moth (Plutella xylostella L.)(DBM). In the first study, plants were exposed to high and low light intensities during different times of the year, resulting in a range of light intensities. From four experiments, plants exhibited higher phenolic content, greater shoot biomass, and higher C:N ratios under high light intensity, whereas plants under low light intensity contained higher protein. Ferulic acid increased under high light intensity, and this increase was negatively correlated with male DBM body weights. However, DBM developed faster on plants in the August experiment (high light), compared to the July experiment (lower light). This implies that light intensity may not be affecting DBM through plant-mediated changes unless reduced male weights confer a reduction in larval consumption. In the nitrogen source study, application of an organic source of nitrogen (fish hydrolysate fertilizer) was compared to a conventional fertilizer to determine whether nitrogen source directly impacts pac choi chemistry and biomass, thus indirectly impacting DBM fitness. In two experiments, there was no significant effect of fertility treatment on pac choi nutrients or biomass, with the exception of percent leaf phosphorus, which was significantly higher in the conventional fertility treatment. For DBM, percent survival and cohort development were significantly reduced on pac choi receiving the organic fertilizer. Calcium and magnesium were significantly higher in pac choi infested with DBM larvae than plants without DBM. In addition, calcium was negatively correlated with female DBM body weights in one experiment for the organic treatment. Overall, this study demonstrated that pac choi plants that received the organic fertilizer were similar to pac choi plants that received a conventional fertilizer with the exception of phosphorus. Furthermore, female DBM body weights were negatively impacted by calcium in the organic treatment. As multiple fitness traits for DBM were negatively affected in the organic treatment, pac choi crops grown with fish hydrolysate fertilizer may experience less feeding from DBM.
Keywords: Plutella xylostella; Diamondback moth; Brassica rapa; Pac choi; Plant-insect interactions; Light intensity; Agriculture, General (0473); Ecology (0329); Entomology (0353)